Palgrave handbook of international trade - Bernhofen, Daniel M. (Palgrave Macmillan, 2011)
"International trade is the core foundation of globalization. This current and up-to-date volume brings together the finest academics working in the field today, containing contributions in key areas of policy research, such as, modelling frameworks, trade policy, trade and migration, trade and the environment, trade and unemployment"